Manajemen Nutrisi pada Bayi BBLSR dengan Pemberian Fortifikasi ASI, Susu formula, dan ASI - Sayyida Nafisa; Ferika Indarwati; Layli Anisah (An Idea Health Journal, 2025)
A very low birth weight infant (VLBW) with a birth weight of <1500 grams has extremely low nutrient reserves, such as calcium, phosphate, iron, zinc, and vitamins, with little to no subcutaneous fat and glycogen stores. The management of VLBW infants focuses on providing nutrition through fortification, formula milk, or breast milk if lactation is sufficient. This study aims to examine the impact of weight management in VLBW infants through the administration of fortification, formula milk, and breast milk.This research employs a case study method by administering fortified breast milk, formula milk, and breast milk over ten days to a VLBW infant treated in the PICU-NICU of Temanggung Regional Hospital. The results show that after receiving fortified breast milk, the infant’s weight increased by 70 grams. When given formula milk, there was no weight gain, while breast milk administration resulted in a weight gain of 75 grams. These findings indicate that breast milk provides the most significant weight gain without causing weight loss, although the increase occurs gradually.It is recommended that parents of VLBW infants optimize weight gain by providing exclusive breastfeeding, either directly or indirectly, if the infant has difficulty nursing.